Risk Analysis of Equipment Loss During Marine Survey Operation by Integrating Fault Tree to Bayesian Network - Waskito, Dwitya Harits; Muhtadi, Ahmad; Prasetyo, Dimas Fajar; Kurniawan, Indra; Haryanto, Dwi; Riyadi, Adi Slamet (Pusat Publikasi Ilmiah Institut Teknologi Sepuluh Nopember, 2024)
The process of deploying and towing the survey equipment for several marine survey activities is essential since it visualises the seabed and improves data accuracy. Since the equipment is deployed to an underwater level, the risk arises with the deployment. These risks include potential contact with submerged objects and the seabed, which can result in the loss of equipment and have detrimental environmental consequences. This study aims to analyse the risk-associated factors related to the loss of survey equipment using Fault Tree Analysis (FTA) and Bayesian Network (BN). The constructed FTA was converted into BN to find the relationship between Basic events and simulate the probability of updating Basic events. The sensitivity analysis results of the BN model indicate that